Development and evaluation of two simple, rapid immunochromatographic tests for the detection of Yersinia pestis antibodies in humans and reservoirs. - Minoarisoa Rajerison; Sylvie Dartevelle; Lalao A Ralafiarisoa; Idir Bitam; Thi Ngoc Tuyet Dinh; Voahangy Andrianaivoarimanana; Faridabano Nato; Lila Rahalison (Public Library of Science (PLoS), 2009)
BACKGROUND: Tools for plague diagnosis and surveillance are not always available and affordable in most of the countries affected by the disease. Yersinia pestis isolation for confirmation is time-consuming and difficult to perform under field conditions. Serologic tests like ELISA require specific equipments not always available in developing countries. In addition to the existing rapid test for antigen detection, a rapid serodiagnostic assay may be useful for plague control. METHODS/PRINCIPAL FINDINGS: We developed two rapid immunochromatography-based tests for the detection of antibodies directed against F1 antigen of Y. pestis. The first test, SIgT, which detects total Ig (IgT) anti-F1 in several species (S) (human and reservoirs), was developed in order to have for the field use an alternative method to ELISA. The performance of the SIgT test was evaluated with samples from humans and animals for which ELISA was used to determine the presumptive diagnosis of plague. SIgT test detected anti-F1 Ig antibodies in humans with a sensitivity of 84.6% (95% CI: 0.76-0.94) and a specificity of 98% (95% CI: 0.96-1). In evaluation of samples from rodents and other small mammals, the SlgT test had a sensitivity of 87.8% (95% CI: 0.80-0.94) and a specificity of 90.3% (95% CI: 0.86-0.93). Improved performance was obtained with samples from dogs, a sentinel animal, with a sensitivity of 93% (95% CI: 0.82-1) and a specificity of 98% (95% CI: 0.95-1.01). The second test, HIgM, which detects human (H) IgM anti-F1, was developed in order to have another method for plague diagnosis. Its sensitivity was 83% (95% CI: 0.75-0.90) and its specificity about 100%. CONCLUSION/SIGNIFICANCE: The SIgT test is of importance for surveillance because it can detect Ig antibodies in a range of reservoir species. The HIgM test could facilitate the diagnosis of plague during outbreaks, particularly when only a single serum sample is available.